Identification of a small molecule 0390 as a potent antimicrobial agent to combat antibiotic-resistant Escherichia coli - Li, Linhui; She, Pengfei; Liu, Shasha; Li, Yimin; Li, Zehao; Yang, Yifan; Zhou, Linying; Wu, Yong (Frontiers in Microbiology, 2022)
Introduction Antibiotic resistance has posed a serious challenge to global public health. With the increasing resistance emergence of E. coli and mortality caused by drug-resistant E. coli infections, it is urgent to develop novel antibiotics. Methods By high-throughput screening assay, we found a bioactive molecule, 0390 (6056–0390), which demonstrated antimicrobial effects against E. coli. The antimicrobial effects of 0390 alone or in combination with conventional antibiotics were assessed by scanning electron microscopy, transmission electron microscopy, drug combination assay, and growth inhibition assay. In addition, we investigated the antimicrobial efficacy in subcutaneous infection model in vivo Results 0390 showed significant synergistic antimicrobial effects in combination with SPR741, a polymyxin B derivative, against E. coli standard strain and extensively drug-resistant (XDR) clinical isolates, and the combination exhibited good safety property in vitro. In addition, we demonstrated that the combinational treatment of 0390 and SPR741 exhibited a considerable antibacterial activity in vivo, and no tissue damage or other toxicity was observed after the therapeutic dose treatment. Discussion To confront the issue of the infectious diseases related to E. coli and its multidrug resistant strains, potential approaches, such as new antibacterial agents with different structures from conventional antibiotics and drug combinations, are urgently needed. In this study, we have determined the in vitro and in vivo antimicrobial potential of 0390 alone or in combination with SPR741, which might be used as a treatment option for E. coli related infections.